Management Accounting Improvement in Packaged Beverage Entities - Hartika, Lia; Dithisari, Indri (Frontier Management Science, 2024)
Management accounting practices must be embedded and running in a corporate entity or organization. Management accounting can provide actual information that affects the decision-making process of a company manager. One of the implementations is the concept of management in entities in the packaged beverage industry. The process of handling customers must continue to be carried out because the customers have several characteristics, such as loyalty, behavior, habits, and perceptions of a product. At the same time, the company must apply ideas to the company's production activities and be able to analyze the social, economic, and environmental impacts of these activities. So in this study, the production service sector that the author has chosen is packaged beverage industry because, since the COVID-19 pandemic, beverage producer companies have changed their business methods, namely through online ordering applications or package systems. This habit has not changed after the COVID-19 pandemic. Online sales of packaged beverages are still often carried out by the public. There is a change in economic behavior in the community, and it has a direct impact on the business model and product sales of the packaged beverage manufacturer. Based on this background, the authors will conduct research, namely to determine what variables will affect this business so that packaged drinks continue to be favored by the community so as to grow economic potential and job opportunities for the community.